Inovasi Program Menghafal Al-Qur’an di Pesantren Dar Al-Dzikra Assunniyyah Wonorejo Kencong - Hidayati, Titin Nur; Rahma, Fathur (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2023)
Most Islamic boarding schools innovate by including Al-Qur'an memorization activities as one of the superior programs that receive special attention. Public interest in the Tahfidz Al-Qur'an program is getting bigger day by day. The proof is that many parents choose Islamic boarding schools that have the tahfidz Al-Qur'an program in them as a priority choice for their children, so that their children will later become Muhafidz Qur'ans who will certainly be the pride of their parents, especially in the afterlife. But memorizing the Qur'an is not an easy thing as easy as turning our palms. There are many processes that we have to go through in it. So using the right method and carrying out several innovations in it will facilitate our steps in getting the maximum quality of memorization. The commitment to maintaining a lifetime of memorization must also be instilled so that this awareness grows automatically within ourselves. This research paper will discuss the meaning of memorizing the Qur'an, the legal basis for memorizing the Qur'an, various methods of choice in memorizing the Qur'an, the methods applied at the Tahfidz Al-Qur'an Dar al-dzikra Assunniyyah Islamic Boarding School and innovation provided by Islamic boarding schools to produce superior and competent hafidz Qur'an graduates.